How Far Has Audit Quality been Researched? - Muhammad Taqi (Journal of Islamic Economics Literatures, 2020)
The audit has a significant function as an instrument of external corporate governance, and audit quality. Affect audit governance. The overall objective of the audit is to obtain reasonable assurance that the financial statements do not contain substantial misstatements due to fraud or error, to issue an audit report following auditing standards. This study aims to determine the development map of audit quality research that is indexed by Scopus and other reputable journals with the keyword "Audit Quality". The data analyzed were 893 selected publications. The development map of audit quality research was analyzed using the VOSviewer application program to find out the bibliometric map. The results showed that the number of publications on the development of audit quality research indexed Scopus from the last 5 years since 2017-2021 experienced a significant increase and the words most used by the author are audit quality, human, dan clinical audit.